Ultrasound-Guided Sural Nerve and Tibial Nerve Block Provides Comparable Analgesia to Popliteal Sciatic Nerve Block Following Calcaneal Surgery: A Single Center Randomized Controlled Double-Blind Study - Yao J; Cai J; Lu Q; Huang X (Journal of Pain Research)
Jun Yao,1,2,* Jialin Cai,2,* Qingwang Lu,2 Xiaojing Huang3 1Department of Anesthesiology, Shanghai Jiao Tong University Affiliated Sixth People’s Hospital, Shanghai, 200233, People’s Republic of China; 2Department of Anesthesiology, Jinjiang Municipal Hospital (Shanghai Sixth People’s Hospital Fujian Campus), Shanghai, Fujian, 362200, People’s Republic of China; 3Department of Pain Medicine, Shanghai Geriatric Medical Center, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaojing Huang, Department of Pain Medicine, Shanghai Geriatric Medical Center, No. 2560 Chunshen Road, Minhang District, Shanghai, 201104, People’s Republic of China, Email anesthesiahuang@163.comBackground: Popliteal sciatic nerve blocks have gained popularity as an anesthesia choice for calcaneal surgery. While the simpler technique of sural and tibial nerve blocks offers potential, its safety and efficacy require validation through a head-to-head clinical study. This study compared the efficacy of ultrasound-guided sural and tibial nerve blocks (ST) with popliteal sciatic nerve block (PS) for operative and postoperative analgesia.Methods: A total of 80 patients (40 per group) undergoing calcaneal surgery were randomized to receive either ST or PS nerve blocks. Patients in both groups were provided with an intravenous patient-controlled analgesia (PCA) device containing flurbiprofen. Visual analogue scale (VAS) pain scores were recorded at awakening, 2, 6, 12, and 24 h postoperatively. In addition, block onset time, procedure duration, patient satisfaction, and application of postoperative analgesics were also recorded.Results: VAS scores were comparable between groups throughout the 24-hour observation period (VAS range 0– 3, p > 0.05). ST blocks demonstrated faster onset (8.2 ± 1.5 vs 12.4 ± 2.1 minutes, p< 0.001) and shorter procedure time (11.5 ± 2.1 vs 16.8 ± 2.4 minutes, p< 0.001). Patient satisfaction scores were similar between groups (8.5 ± 0.8 vs 8.3 ± 0.9, p=0.31).Conclusion: Ultrasound-guided sural and tibial nerve blocks provide effective operative and postoperative analgesia comparable to popliteal sciatic nerve block. The blocks are easy to perform, have a faster onset, and achieve high patient satisfaction, making them a valuable alternative for calcaneal surgery.Keywords: calcaneal surgery, ultrasound-guided, popliteal sciatic nerve block, tibial nerve block, sural nerve block